Eficiência de seis métodos de extração na recuperação de nematóides, de diferentes gêneros, de três tipos de solos - Mendes, Maria de Lourdes; Ferraz, Silamar; Regazzi, Adair José (Revista Ceres, 2025)
A sandy soil (71% sand), a clay soil (28% sand) and a mixture of them (49% sand) were used to compare the efficiency of six methods of extraction on four genera of plant parasitic nematodes. Fifty grams of each soil sample were artificially infested with 500 + 10 Tylenchorhynchus sp., Helicotylenchus sp. and Nothocriconema sp and 250 * 10 second stage larvae of Meloidogyne javanica. Greater recovery of Tylenchorhynchus was verified in the sandy soil whereas Meloidogyne larvae were more efficiently extracted from clay soil, with all six methods. The recovery capacity of all methods was below 50%, except Cobb’s decanting and sieving technique when used for Tylenchorhynchus sp. As expected, Baermann's funnel and their variants did not recover Nothocriconema; however Oostenbrink’s cotton filter was an exception. In general, Cobb's method as well as centrifugal flotation recovered more nematodes than the other methods, the latter being more convenient to use due to a clearer nematode suspension at the end.